Antimicrobial Properties of Cocos Nucifera (Coconut) Husk; Potential Applications in The Prevention and Treatment of Food Pathogens (International Journal of Scientific Research in Science and Technology, 2026)
The increasing prevalence of antibiotic-resistant pathogens has intensified the search for natural antimicrobial agents. Cocos nucifera (coconut) husk, a traditionally discarded byproduct, has demonstrated promising antimicrobial properties due to its rich composition of bioactive compounds, including phenolic, flavonoids, tannins, and lignin. This study explores the antimicrobial potential of coconut husk extracts against foodborne pathogens, highlighting their possible applications in food preservation. Studies have reported significant antibacterial and antifungal activities of coconut husk extracts against common pathogens such as Bacillus paramycoides. Potential applications include its use as a natural food preservative. Further research is necessary to optimize extraction methods, assess toxicity levels, and validate clinical efficacy to enhance the utilization of coconut husk as a sustainable antimicrobial agent.